2016
DOI: 10.1016/j.jgr.2015.08.006
|View full text |Cite
|
Sign up to set email alerts
|

A single-center, randomized, double-blind, placebo-controlled study on the efficacy and safety of “enzyme-treated red ginseng powder complex (BG11001)” for antiwrinkle and proelasticity in individuals with healthy skin

Abstract: BackgroundDuring the aging process, skin shows visible changes, characterized by a loss of elasticity and the appearance of wrinkles due to reduced collagen production and decreased elasticity of elastin fibers. Panax ginseng Meyer has been used as a traditional medicine for various diseases due to its wide range of biological activities including skin protective effects. Ginsenosides are the main components responsible for the biological activities of ginseng. However, the protective activities of an enzymati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Similarly, Asian individuals are also classified as having skin of color and, to date, just a few studies have examined the effects of skin aging on this diverse population. Skin elasticity is compromised in photoaged Asian facial skin (Ahn et al, 2007;Nam et al, 2014;Park et al, 2016); however, it remains unknown to what extent other biomechanical properties are affected. Performing a thorough assessment of both biomechanical and histologic analyses of young and aged Asian skin is therefore warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Asian individuals are also classified as having skin of color and, to date, just a few studies have examined the effects of skin aging on this diverse population. Skin elasticity is compromised in photoaged Asian facial skin (Ahn et al, 2007;Nam et al, 2014;Park et al, 2016); however, it remains unknown to what extent other biomechanical properties are affected. Performing a thorough assessment of both biomechanical and histologic analyses of young and aged Asian skin is therefore warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Although BIOGF1K was revealed not to have direct suppressive action on melanin formation and tyrosinase activity, present results seem to raise a possibility that BIOGF1K can have another potential merit for the development of cosmetic products in addition to its antiphotoaging properties. In fact, numerous cosmetic products contain fractions previously prepared in Korea from P. ginseng (e.g., BG11001, P. ginseng berry, and AP-SF) [48] , [49] , [50] . Studies on individual compounds from P. ginseng have indicated that ginsenosides (G)-Rg2, G-F2, G-Re, and G-Rb2 protect skin and possess additional cosmeceutical activities by suppressing melanin biosynthesis, enhancing cyclic growth of hair follicles, improving skin barrier function, and suppressing skin inflammation [51] , [52] , [53] .…”
Section: Discussionmentioning
confidence: 99%
“…Red ginseng is known to have antiaging effects. Ginseng can protect the epidermal and dermal layers of the skin from strong UV-B radiation [11] , while maltol, one of the phenolic compounds present in red ginseng, reduces fatigue and exhibits antioxidant properties [12] . In addition, ginseng extracts, including ginsenosides Re, Rc, and Rb1, induce procollagen type I–related gene expression and decrease that of matrix metalloproteinase 1 and tumor necrosis factor [13] .…”
Section: Introductionmentioning
confidence: 99%